Determining University Students’ Attitudes Towards Dating Violence - DOST, Ayşe (Göbeklitepe Medical Science Journal, 2021)
Objective: In this study, it was aimed to determine the attitudes of university students towards dating violence. Method: The study was conducted with 432 students studying at a health sciences school of a foundation university in the spring semester of the 2020-2021 academic year. Data were collected using the "personal information form" and the "Dating Violence Attitude Scale" form. Results: It was determined that 7.9% of the students were exposed to psychological violence and 3.7% of them were exposed to physical violence. Students’ emotional violence sub-dimension score 27.03±4.58, sexual violence sub-dimension score 33.03±3.57, general violence sub-dimension score 24.38±2.96, physical violence sub-dimension score 23.81±3.24, economic violence sub-dimension score was 21.13±3.49, and the scale total score was 129.38±11.14 points. It was determined that the mean rank of the emotional violence sub-dimension of the students who stated that they lived in the village was higher, and the mean rank of the sexual violence sub-dimension of the students who stated that their current dating relationship was 3 years or more (p<0.05). Conclusion: In the study, it was determined that students’ attitudes towards dating violence were not supportive, and there is a need for the development of programs to prevent dating violence and experimental studies to be carried out.